Verbascum rotundifolium subsp. haenseleri (Boiss.) Murb. (Scrophulariaceae), an overlooked taxon in the Portuguese flora - Carapeto, André; Serafim, João (UMA Editorial, 2024)
Verbascum rotundifolium subsp.haenseleri (Boiss.) Murb. was first collected in Portugal in 1970 (in Beira Baixa) but has remained uncited in all reference works regarding the Portuguese flora. In recent years, the plant was observed in Beira Baixa at four distinct sites along the valley of the Erges river. This plant is not an occasional or vagrant species in Portugal and, thus, should be considered as native and added to the Portuguese flora.

Verbascum rotundifolium Ten. fue recolectada por primera vez en Portugal en 1970 (Beira Baixa), pero permaneció ausente de todos los trabajos de referencia sobre la flora portuguesa. En los últimos años, la planta también fue observada en la Beira Baixa en cuatro sitios distintos en el valle del río Erges. La planta no es una especie ocasional ni adventicia en Portugal por lo que debe considerarse nativa y agregarse a la flora portuguesa.
Verbascum rotundifolium subsp. haenseleri (Boiss.) Murb. (Scrophulariaceae), un taxon ignorado en la flora portuguesa
Keywords: Escrofulariáceas - Distribución geográfica; Especies exóticas invasoras; Fitogeografía; Gordolobo; Río Erges; Portugal; Ciencia ciudadana